2017
DOI: 10.1021/acs.bioconjchem.7b00178
|View full text |Cite
|
Sign up to set email alerts
|

Bisazide Cyanine Dyes as Fluorogenic Probes for Bis-Cyclooctynylated Peptide Tags and as Fluorogenic Cross-Linkers of Cyclooctynylated Proteins

Abstract: Herein we present the synthesis and fluorogenic characterization of a series of double-quenched bisazide cyanine probes with emission maxima between 565 and 580 nm that can participate in covalent, two-point binding bioorthogonal tagging schemes in combination with bis-cyclooctynylated peptides. Compared to other fluorogenic cyanines, these double-quenched systems showed remarkable fluorescence intensity increase upon formation of cyclic dye-peptide conjugates. Furthermore, we also demonstrated that these bisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
1
20
0
1
Order By: Relevance
“…The fluorescence of fluorogenic scaffolds can be quenched by several means, for example, by photoinduced electron transfer [5a], twisted intramolecular charge transfer [5b], energy transfer [5c], or by moieties that suppress fluorescence by opening non‐radiative relaxation pathways by biasing vibrational release of energy [5d]. Azide derived fluorogenic frames are of special importance as they can be applied in biorthogonal labeling schemes due to the two‐in‐one feature of this small, biologically inert, yet highly energetic function being a biorthogonal handle and a quencher moiety at the same time . The excitation and emission wavelengths of coumarin based dyes can be easily shifted towards the biologically more advantageous red regime by extension of the conjugated system as part of polymethine chains.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence of fluorogenic scaffolds can be quenched by several means, for example, by photoinduced electron transfer [5a], twisted intramolecular charge transfer [5b], energy transfer [5c], or by moieties that suppress fluorescence by opening non‐radiative relaxation pathways by biasing vibrational release of energy [5d]. Azide derived fluorogenic frames are of special importance as they can be applied in biorthogonal labeling schemes due to the two‐in‐one feature of this small, biologically inert, yet highly energetic function being a biorthogonal handle and a quencher moiety at the same time . The excitation and emission wavelengths of coumarin based dyes can be easily shifted towards the biologically more advantageous red regime by extension of the conjugated system as part of polymethine chains.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kele et al . reported a series of bis‐azide‐containing DCF linkers based on cyanine (DCF1‐DCF5) and coumarin (DCF6) scaffolds, and demonstrated that these linkers possessed double‐caging features, as evidenced by the nonfluorescent nature of single click intermediates.…”
Section: Fluorogenic Bifunctional Linkersmentioning
confidence: 99%
“…Doubly caged bis‐azide cyanine linkers (DCF1–DCF5) and coumarin linker (DCF6) were utilized for one‐pot covalent dimerization of GFP‐BCN and intramolecular cyclization of dicyclooctyne‐modified peptides (BCN‐POI‐BCN). These DCF linkers exhibited remarkable emission enhancement upon consumption of both azide moieties, which enabled optical tracking of the conjugation process …”
Section: Fluorogenic Bifunctional Linkersmentioning
confidence: 99%
See 2 more Smart Citations